Friends with boys - Hicks, Faith Erin. (New York : First Second, 2012)
After an idyllic childhood of homeschooling with her mother and three older brothers, Maggie enrolls in public high school, where interacting with her peers is complicated by the melancholy ghost that has followed her throughout her entire life.
Keywords: Graphic novels; Ghosts -- Fiction; Interpersonal relations -- Fiction; High schools -- Fiction; Schools -- Fiction; Brothers and sisters -- Fiction; Graphic novels